Dietary Compounds Influencing the Sensorial, Volatile and Phytochemical Properties of Bovine Milk - Clarke, Holly J.; Griffin, Carol; Rai, Dilip K.; O’Callaghan, Tom F.; O’Sullivan, Maurice G.; Kerry, Joseph P.; Kilcawley, Kieran N. (Molecules (Basel, Switzerland), 2019)
The main aim of this study was to evaluate the volatile profile, sensory perception, and phytochemical content of bovine milk produced from cows fed on three distinct feeding systems, namely grass (GRS), grass/clover (CLV), and total mixed ration (TMR). Previous studies have identified that feed type can influence the sensory perception of milk directly via the transfer of volatile aromatic compounds, or indirectly by the transfer of non-volatile substrates that act as precursors for volatile compounds. In the present study, significant differences were observed in the phytochemical profile of the different feed and milk samples. The isoflavone formonoetin was significantly higher in CLV feed samples, but higher in raw GRS milk, while other smaller isoflavones, such as daidzein, genistein, and apigenin were highly correlated to raw CLV milk. This suggests that changes in isoflavone content and concentration in milk relate to diet, but also to metabolism in the rumen. This study also found unique potential volatile biomarkers in milk (dimethyl sulfone) related to feeding systems, or significant differences in the concentration of others (toluene, p-cresol, ethyl and methyl esters) based on feeding systems. TMR milk scored significantly higher for hay-like flavor and white color, while GRS and CLV milk scored significantly higher for a creamy color. Milk samples were easily distinguishable by their volatile profile based on feeding system, storage time, and pasteurization.